Calcification of heart structures in patients with suspected coronary heart disease depending on renal function - O.V. Kuryata; I.L. Karavanska; V.V. Semenov; A.M. Nikutova (Medičnì Perspektivi, 2022)
Cardiovascular disease is the leading cause of death in the world. The use of the coronary artery calcification score (CACS) allows to determine the risk of coronary artery disease (CAD). Chronic kidney disease (CKD) is a one of the major risk factors for coronary artery disease. With a decrease in renal function, impaired calcium-phosphorus metabolism leads to excessive tissue calcification. It is likely that patients with different kidney function experience different types of calcium deposition. The use of CACS is an opportunity to assess the condition of the coronary arteries without using a contrast agent, which is very important for patients with CKD. One of the most accessible and significant research methods for clinical screening use is computed tomography with non-invasive assessment of coronary calcium (quantitative analysis of the calcium index). To evaluate it, the method of A. Agatston is used, which allows to measure calcium in units. Our aim was to investigate the pattern of calcification of heart structures depending on renal function in patients with suspected coronary heart disease. The patients in the presented study had a high incidence of diabetes mellitus (49.4%) and arterial hypertension (83.1%). In patients with suspected coronary artery disease, borderline values of systolic and diastolic blood pressure and total cholesterol were found. In the majority of the patients CACS was 1-100 Agatston units (AU). After the distribution of patients into groups depending on glomerular filtration rate (GFR), it was found that the groups of patients with lower GFR, were of older age. The proportion of patients with total CACS >100 AU was the highest in the group of patients with GFR 30-59 ml/min. There were no significant differences in the structure of general and vascular CACS between patients with GFR 90-120 ml/min and GFR 60-89 ml/min. Valvular CACS was significantly lower in patients with GFR <60 ml/min. In all cases of visual comparison of CACS depending on GFR, significantly higher CACS indices differed in patients with GFR <60 ml/min compared to patients with GFR ≥60 ml/min.